THE CHANGE OF THE EARTH MAGNETIC MOMENT AND CLIMATE IN THE PLEISTOCENE - Petrova G.N.; Pilipenko O.V.; Raspopov O.M.; Trubikhin V.M. (My University, 1999)
A composite curve was plotted for the dependence of VADM on the age for the last 450 thousand years, using 21 curves available for various regions of the globe. The correlation between the variations in the magnetic field and climate changes is clearly manifested for the time periods of 90-0 and 342-198 thousand years. The time intervals including the Blake, Biva-I, and Biva-III excursions show changes in the correlation sign.
Keywords: EARTH MAGNETIC MOMENT; CLIMATE IN THE PLEISTOCENE; CLIMATE CHANGES; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен